2014
DOI: 10.3109/07357907.2014.911881
|View full text |Cite
|
Sign up to set email alerts
|

Association Between theNFKB1-94ins/del ATTG Polymorphism and Cancer Risk: An Updated Meta-Analysis

Abstract: To assess the effect of the NFKB1 -94ins/del polymorphism on cancer, we conducted a meta-analysis based on 25 studies including 8,750 cases and 9,170 controls. Overall, the -94ins/del polymorphism was associated with cancer risk in the pooled analysis and in Asian population, whereas no association was observed in Caucasian population. Stratified analysis by subtypes of cancer showed that the -94ins/del polymorphism was associated with oral squamous cell carcinoma and ovarian cancer risk, but had no associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 48 publications
1
13
1
Order By: Relevance
“…This notion is consistent with a recent study showing that the reduced lifespan of nfkb1 −/− mice could be attributed to chronic, progressive low‐grade inflammation and premature ageing 14 . Interestingly, in humans (certain Asian populations) the NF‐κB1 ‐94ins/del promoter polymorphism, resulting in reduced NF‐κB1 protein expression, is associated with increased cancer risk 44 . Thus, constitutive drug‐mediated inhibition of NF‐κB1 may exacerbate certain autoimmune pathologies by increasing inflammation and may also increase the risk of malignancy.…”
Section: Discussionsupporting
confidence: 91%
“…This notion is consistent with a recent study showing that the reduced lifespan of nfkb1 −/− mice could be attributed to chronic, progressive low‐grade inflammation and premature ageing 14 . Interestingly, in humans (certain Asian populations) the NF‐κB1 ‐94ins/del promoter polymorphism, resulting in reduced NF‐κB1 protein expression, is associated with increased cancer risk 44 . Thus, constitutive drug‐mediated inhibition of NF‐κB1 may exacerbate certain autoimmune pathologies by increasing inflammation and may also increase the risk of malignancy.…”
Section: Discussionsupporting
confidence: 91%
“…These findings were also specific to the Asian population. Duan et al [31] reviewed a total of 25 studies that included 8,750 cancer cases and 9,170 controls. They found that the insertion allele of the -94ins/delATTG polymorphism significantly increased cancer risk, both in overall genetic analysis as well as in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that geographical, lifestyle and ethnic differences can impact on genetic/molecular pathways in head and neck squamous cancers [3237]. Majority of these studies investigated genetic DNA polymorphisms but none of them, to our knowledge, compared gene expression levels in HNSCC.…”
Section: Discussionmentioning
confidence: 99%